PENINGKATAN HASIL BELAJAR KETERAMPILAN BERPIKIR KRITIS PADA BIDANG STUDI IPA MELALUI METODE PEMBELAJARAN BERBASIS INKUIRI - Ahmad Syachruroji (JPsd (Jurnal Pendidikan Sekolah Dasar), 2015)
The objective of this research is to know: The learning process to increase elementary student learning critical thingking skills outcomes in science study through “inquiry based learning methods”. About thirty three students of  SD Terpadu Al Qudwah Rangkasbitung Banten are the subject of these research. The research uses action research method by Kemmis and Mc Taggart that consist of four steps: planning, action, observation, and reflection. Data collecting technique uses field notes, interview, documentation, and observation. This research also uses quantitative analysis. The result of the research describes that ”inquiry based learning methods” in science study gives impact for increasing elementary student learning critical thingking skills outcomes in science study. The research result showed that the student’s outcome of critical thinking skill was 93,94% in the second cycle. Keyword: student’s outcome of critical thinking skill, inquiry based learningmethods